Eight weeks of high-intensity interval vs. sprint interval training effects on overweight and obese adolescents carried out during the cool-down period of physical education classes: randomized controlled trial - Noelia González-Gálvez; Antonio Soler-Marín; Tomás Abelleira-Lamela; Lucia Abenza-Cano; Adrián Mateo-Orcajada; Raquel Vaquero-Cristóbal (Frontiers Media S.A., 2024)
ObjectiveThe aim of this study was to evaluate the effect of sprint interval training (SIT) and [high intensive interval training (HIIT)] carried out during the cool-down period of the physical education classes on body composition, blood pressure variables (BP) and pulse rate (PR), and cardiorespiratory fitness of adolescents who are overweight and obese, and to compare the differences in enjoyment in response to SIT vs. HIIT.MethodsFor this randomized controlled trial, forty-five adolescents were recruited from a high school and were randomly placed into three groups. SIT and HIIT trained for 8 weeks, twice a week, for 12 min/session. Experimental group (EG) 3 was the control, and they maintained their regular physical education class schedule. The SIT group performed 6 sets of 60 s of work (90-95%HRmax) / 60 s of rest (50-55%HRmax), and the HIIT group performed 3 sets of 2 min of work (80-85%HRmax) / 2 min of rest (50-55%HRmax).ResultsBoth experimental groups showed a significant improvement in fat mass (FM) (%) and trunk FM (kg). In addition, EG2 reported a significance improvement in lean mass (kg), blood pressure BP (mmHG), systolic blood pressure (SBP) (mmHg), diastolic blood pressure (DBP) (mmHg), PR (bpm), and VO2max (ml/kg/min).ConclusionThe present study found that a HIIT protocol performed during the cool-down period of the physical education classes generated adaptations such as improvement in body composition, BP variables and PR, and cardiorespiratory fitness, in overweight and obese adolescents. In contrast, the group of overweight and obese adolescents who performed SIT showed limited benefits, with changes in fat mass only.